2009
DOI: 10.1016/j.cell.2009.06.043
|View full text |Cite
|
Sign up to set email alerts
|

The Exosome Regulates Circadian Gene Expression in a Posttranscriptional Negative Feedback Loop

Abstract: Summary The eukaryotic circadian oscillators consist of autoregulatory negative feedback loops. However, little is known about the role of post-transcriptional regulation of RNA in circadian oscillators. In the Neurospora circadian negative feedback loop, FRQ and FRH form the FFC complex that represses frq transcription. Here we show that FFC also binds frq RNA and interacts with the exosome to regulate frq RNA decay. Consequently, frq RNA is robustly rhythmic as it is more stable when FRQ levels are low. Sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
130
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 54 publications
5
130
0
Order By: Relevance
“…It has been suggested that the FFC facilitates rhythmic turnover of frq RNA 14 . The mutant frq 9 allele expresses full-length RNA but, due to a frameshift mutation, it encodes a truncated FRQ 9 protein that does not associate with FRH 14 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that the FFC facilitates rhythmic turnover of frq RNA 14 . The mutant frq 9 allele expresses full-length RNA but, due to a frameshift mutation, it encodes a truncated FRQ 9 protein that does not associate with FRH 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The mutant frq 9 allele expresses full-length RNA but, due to a frameshift mutation, it encodes a truncated FRQ 9 protein that does not associate with FRH 14 . We inhibited transcription in WT and frq 9 strains with thiolutin 14 and found that the turnover kinetics of frq and frq 9 RNA was similar ( Supplementary Fig. 2a), suggesting that the FFC may not regulate turnover of frq RNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[50][51][52] Phosphorylation plays a pivotal role in regulating the activity and abundance of clock components. The abundance of some circadian clock-associated proteins, including LHY, CASEIN KINASE 2B4 (CKB4) and XAP5 CIRCADIAN TIMEKEEPER, is modulated by phosphorylation.…”
Section: Fine-tuning Of Protein Activity and Degradation In The Circamentioning
confidence: 99%